2015
DOI: 10.1038/srep10032
|View full text |Cite
|
Sign up to set email alerts
|

How does public opinion become extreme?

Abstract: We investigate the emergence of extreme opinion trends in society by employing statistical physics modeling and analysis on polls that inquire about a wide range of issues such as religion, economics, politics, abortion, extramarital sex, books, movies, and electoral vote. The surveys lay out a clear indicator of the rise of extreme views. The precursor is a nonlinear relation between the fraction of individuals holding a certain extreme view and the fraction of individuals that includes also moderates, e.g., … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 40 publications
(72 reference statements)
1
64
0
6
Order By: Relevance
“…Centola and Baronchelli (2015) suggested that the increase in social connectedness via social media could potentially facilitate the convergence of public opinion among people who do not even know that they are implicitly coordinating with one another. Other studies show that such convergence can induce a phase transition (or non-linearity), shifting public opinion from moderate views towards extremism (Ramos et al, 2015), causing community disconnection (Gil and Zanette, 2006) and echo-chamber effects, particularly in domains with high emotional salience (Cowan, 2014;Jasny et al, 2015;Pentland, 2014). We will conclude by presenting a coarse outline for technical approaches to counteract imbalances in online communication systems.…”
Section: Practical Implications For Improving Online Communication Symentioning
confidence: 99%
“…Centola and Baronchelli (2015) suggested that the increase in social connectedness via social media could potentially facilitate the convergence of public opinion among people who do not even know that they are implicitly coordinating with one another. Other studies show that such convergence can induce a phase transition (or non-linearity), shifting public opinion from moderate views towards extremism (Ramos et al, 2015), causing community disconnection (Gil and Zanette, 2006) and echo-chamber effects, particularly in domains with high emotional salience (Cowan, 2014;Jasny et al, 2015;Pentland, 2014). We will conclude by presenting a coarse outline for technical approaches to counteract imbalances in online communication systems.…”
Section: Practical Implications For Improving Online Communication Symentioning
confidence: 99%
“…No caso não correlacionado emergem cascatas de ativação com uma distribuição com decaimento em lei de potência com expoente 3/2. De fato, processos de ramificação são o arcabouço de muitos modelos de ativação, produzindo avalanches na mesma classe de universalidade [63,64,102,103,11]. Como consequência, os resultados empíricos se encaixam em um cenário de cascatas de imitação.…”
Section: Discussionunclassified
“…Este trabalho foi desenvolvido parcialmente durante um período de doutorado sanduíche no Levich Institute of New York, onde fui co-orientado pelo Prof. Hernán Makse e pode ser encontrado na Ref. [11].…”
Section: Prefáciounclassified
See 1 more Smart Citation
“…As transições são governadas por uma regra apropriada ao problema de interesse; nosúltimos anos diversas regras foram propostas na literatura [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Referências Bibliográficas 45unclassified